The impact of highly effective modulator therapy on sinusitis and dysosmia in young children with cystic fibrosis: a prospective study protocol - Christine M. Liu; Jakob L. Fischer; Edith T. Zemanick; Jason C. Woods; Karolin K. Markarian; Sean B. Fain; Deborah Froh; Sonya L. Heltshe; Lucas R. Hoffman; Stephen M. Humphries; Elizabeth L. Kramer; Katie Larson Ode; et al. (ERJ Open Research)
Background Chronic rhinosinusitis (CRS) and olfactory dysfunction (OD) are prevalent disease complications in people with cystic fibrosis. These understudied comorbidities significantly impact quality of life. The impact of highly effective modulator therapy (HEMT) in young children with cystic fibrosis (YCwCF) on these disease complications is unknown. This proposed study aims to characterise CRS and OD in YCwCF and assess the efficacy of HEMT in improving sinus and olfactory health in this young age group. Methods This six-centre, prospective, observational study will enrol 80 YCwCF aged 2–8 years. Patients are divided into two groups: those receiving HEMT and those not on HEMT based on clinical indication. Both groups undergo sinus magnetic resonance imaging, psychophysical olfactory tests, and complete patient- or parent-reported quality of life surveys over 2 years. Outcomes will be compared before and after initiation of HEMT and between groups. Ethical approval has been obtained for all sites, and this study has been registered on ClinicalTrials.gov (NCT06191640). Results Enrolment began in April 2023. 21 participants have been enrolled as of October 2023 with ongoing enrolment at all sites. Conclusion This investigation is expected to provide critical insights into the potential benefits of early HEMT initiation in managing CRS and OD in YCwCF. It will assist in developing targeted interventions and contribute to the understanding of HEMT's role in altering the disease course in this demographic.